P312 Efficacy in biologic failure and non-biologic-failure populations in a Phase 3 study of ustekinumab in moderate–severe ulcerative colitis: UNIFI. (25th January 2019) - Sands, B E; Peyrin-Biroulet, L; Marano, C; O'Brien, C D; Zhang, H; Johanns, J; Szapary, P; Rowbotham, D; Leong, R W; Arasaradnam, R P; Danese, S; Van Assche, G; et al.
Abstract: Background: Ustekinumab (UST), an IL12/23 blocker approved for Crohn's disease, was effective in Ph3 induction and maintenance of moderate–severe ulcerative colitis (UC). Efficacy in biologic-failure (BF) and non-biologic-failure (NBF) populations was evaluated. Methods: Pts were randomised to a baseline IV induction UST dose (130 mg or weight-range based doses approximating 6 mg/kg (~6 mg/kg)), or PBO. Responders to UST IV induction entered maintenance and were randomised to SC 90 mg UST (q12wks or q8wks), or PBO. Primary endpoint for wk8 induction and wk44 maintenance was clinical remission. Major secondary endpoints for wk8 induction: endoscopic healing, clinical response, and change from baseline in total IBDQ score and wk44 maintenance: maintenance of clinical response, endoscopic healing, corticosteroid-free clinical remission, and maintenance of clinical remission in baseline remitters. Results: Among patients with documented BF (51.1% of randomised patients), 98.8% had failed at least 1 anti-TNF, 32.6% had failed both anti-TNF and vedolizumab. NBF patients were predominantly bio-naïve (94.3%). In induction, for BF and NBF patients, proportions of patients who achieved clinical remission was significantly greater for UST ~6 mg/kg and 130 mg vs. PBO (BF patients- p < 0.001 for both doses; NBF patients- p < 0.05 for both doses, respectively, Table 1). For BF and NBF patients, major secondary endpoints of clinical response and endoscopic healing and change from baseline in IBDQ were significantly greater for UST ~6 mg/kg and 130 mg vs. PBO (Table 1). Though treatment differences were generally similar between BF and NBF patients, rates were consistently lower for BF patients in each treatment group. In maintenance, for BF and NBF patients, proportions of patients who achieved clinical remission was significantly greater for UST q8w and q12w vs. PBO (BF patients- p < 0.001, p = 0.044, respectively; NBF patients- p = 0.024, p = 0.020, respectively, Table 2). For BF and NBF patients, proportions of patients who achieved each major secondary endpoint was generally greater for UST q8wk and q12wk vs. PBO. In BF patients, the efficacy of UST q8wk was generally greater than UST q12wk (Table 2). Conclusions: UST was effective for induction and maintenance treatment of moderate–severe UC patients with a history of biologic therapy failure (ie, TNF-antagonists and/or vedolizumab) as well as patients without a history of biologic therapy failure who were predominantly bio-naive.